Simulation Analysis Of Denial Of Services At The Computer Network: Simulation Analysis Of Denial Of Services At The Computer Network - Muhammad Amin; Adli Abdillah Nababan (Jurnal Mantik, 2020)
Denial of service is a type of attack whose purpose is to prevent real users from enjoying the services provided by the server. The server is a server that must always be ready to serve user requests, which generally operate 24 hours without stopping. There are several studies on denial of services (DOS) attacks, from research conducted there that examines denial of services (DOS) attacks on web security. Every attack carried out on the web application, every user accessing the web application will occur buffering data so that the user accessing the web application occurs obstacles and even lost data. General problems that occur in the DOS attack detection system (Denial of Services) is a way to prevent DOS attacks that are being carried out on an application or web system with a DOS attack detection system. The simulation of a DOS attack detection system (Denial of Services) made for this research as tool or media to find out DOS attacks that are happening on a local network. Simulation of a DOS (Denial Of Services) attack detection system is expected to be able to analyze every attack that occurs on the network locally and be able to analyze every attack that occurs on a local network simulation. In this research it is expected that the analysis carried out on a DOS attack detection system (Denial of Services) can be used as a reference as a detection of DOS attacks (Denial of Services) in general which is used to detect DOS attacks that occur in other applications